How to Do Things with Sensors - Gabrys, Jennifer (Forerunners: Ideas First, 2019)
An investigation of how-to guides for sensor technologies Sensors are increasingly common within citizen-sensing and DIY projects, but these devices often require the use of a how-to guide. From online instructional videos for troubleshooting sensor installations to handbooks for using and abusing the Internet of Things, the how-to genres and formats of digital instruction continue to expand and develop. As the how-to proliferates, and instructions unfold through multiple aspects of technoscientific practices, Jennifer Gabrys asks why the how-to has become one of the prevailing genres of the digital. How to Do Things with Sensors explores the ways in which things are made do-able with and through sensors and further considers how worlds are made sense-able and actionable through the instructional mode of citizen-sensing projects. Forerunners: Ideas First Short books of thought-in-process scholarship, where intense analysis, questioning, and speculation take the lead